# How to find the y-intercept given #y=4(x-3)^2-1#?

By signing up, you agree to our Terms of Service and Privacy Policy

To find the y-intercept of the equation (y = 4(x - 3)^2 - 1), substitute (x = 0) into the equation and solve for (y).

(y = 4(0 - 3)^2 - 1)

(y = 4(-3)^2 - 1)

(y = 4(9) - 1)

(y = 36 - 1)

(y = 35)

So, the y-intercept is (y = 35).

By signing up, you agree to our Terms of Service and Privacy Policy

- What is the slope of the line passing through # (-4,-8); (0,0) #?
- What is the x intercept in this linear equation y =-4x+4?
- How do you find the slope given 5x+4y=3?
- How do you graph y= 2x-1 on a coordinate graph?
- How do you write the equation of the line in slope intercept form passing through (1, 2) and (2, 5)?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7